Rhetorical Moves in the Abstracts of Arabic Research Articles in Journals Indexed in Scopus and SINTA - Zakia Jauharotul Munfarida; Jenal Bustomi; Muhammad Ibnu Pamungkas (LISANIA: Journal of Arabic Education and Literature, 2026)
This study aims to analyze and compare the rhetorical move structures of Arabic-language journal article abstracts indexed in Scopus and Sinta based on Hyland’s (2000) five-move model. A genre analysis framework using a comparative corpus linguistics method was employed to examine rhetorical structures and linguistic features in academic abstracts. The corpus consists of 35 journal article abstracts selected through purposive sampling, covering Scopus (Q1, Q3, Q4) and Sinta (S1–S6) journals. The data were analyzed to identify the frequency and distribution of each rhetorical move. The findings show high consistency (>86%) in Purpose (Move 2), Method (Move 3), and Product (Move 4) across both groups. Variations appear in contextualization and concluding elements. Sinta journals show higher Move 1 frequency (90%), whereas Scopus journals show lower Move 1 (40%) and higher Move 5 (80%). Differences were identified in rhetorical preferences, particularly in the balance between background information and concluding statements. Move 5 occurred less frequently in the Sinta corpus than in internationally indexed journals, indicating differences in rhetorical emphasis between national and international publication contexts. These findings suggest that internationally indexed journals tend to emphasize research implications and concluding remarks more consistently. Furthermore, the findings may serve as a useful reference for researchers and students in improving the effectiveness and quality of academic abstract writing. The study also contributes to genre analysis research by providing empirical data on rhetorical practices in Arabic-language academic publishing contexts.